Agronomic variability between commercial and experimental carrot genotypes with emphasis on multivariate analysis (Research, Society and Development, 2021)
Carrots are among the five most cultivated vegetables in Brazil, which is why the search for commercial cultivars is a great challenge in breeding programs, because, in addition to being productive, these tuberous roots must present characteristics of fundamental interest for the producer to achieve acceptance of the product in the consumer market. Therefore, the objective of this work was to evaluate the level of similarity between summer carrot genotypes, and to establish the relationships between the variables, through agronomic and morphological characters of the plant and tuberous roots, in order to diagnose possible groupings in relation to the analyzed variables, using the techniques of multivariate and univariate analysis. The trial was conducted in a randomized block design with three replications, evaluating 11 summer carrot genotypes, with seven commercial genotypes available on the market (SV1099DT, Nativa, EX 4098, AGR-123, AGR-125, Juliana and Brazlândia) and four experimental hybrids. Fifteen agronomic characteristics of plants and tuberous roots were evaluated. Given the results, the multiple factor analysis technique was able to establish the similarities between the genotypes studied, showing high similarity between commercial genotypes present in the market and experimental hybrids. Exploratory factor analysis established the correlations of the variables and was able to project a separation between commercial and experimental genotypes. The specificities presented by the experimental genotypes were explained in the Scott-Knott mean test.